Edukasi dan Implementasi Sistem Komposting Rumah Tangga untuk Mengurangi Timbulan Sampah di Desa Kedungsuren, Kaliwungu Selatan, Kendal - Aden Paiq Muntaz; Muhammad Ilham Prasetya; Irgi M. Aqil Daeng Masiga; Eko Setyo Nugroho; Muhammad Zacky Sulthoni; Nabila Mey Nur Hardini; Fatimah Nisa Royyani; Dwi Ayu Novita; Nur Hijratun Nafiah; Itsna Cholifatun Nisa; Nadya Sya’ada; Anisa Badriyah; Avika Fitriana Assari; Shovi Zaidatul Ma’rifah; Aulia Najwa Zaen; Najichah Najichah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Abstract: The purpose of this study was to determine how the influence of the work environment on the loyalty of the Semarang Provincial Social Service. This research uses quantitative research approach with questionnaire method. The population in this study is the Social Rehabilitation and Social Empowerment division at the Central Java Provincial Social Service with a sample of 30 respondents from the two divisions. The sample for this study was selected using a random sampling procedure. By using SPSS 27.0 for Windows, data will be collected through questionnaires that have gone through Descriptive tests, Assumption Tests, Norma;itas Tests, Linearity Tests, Correlation Tests, and Regression Tests. Based on the results of all the tests mentioned above, the loyalty of employees of the Central Java Provincial Social Service is positively and significantly influenced by the work environment at the Central Java Provincial Office.